Analisa dan Implementasi Sistem Informasi Penjualan Obat Berbasis Web Pada Apotik Rakyat Bekasi - Novita Indriyani; indarti indarti (LPPM Universitas Bina Sarana Informatika, 2019)
Pharmacy Information system currently uses a manual system in recording sales transactions and drug stok records. Besides being inefficient, the use of manual systems also requires a lot of energy and time so that work effectivenes is not achieved. Drug sales information system at the Bekasi people’s Pharmacy covers the sales process, the payment process to the making of a recapitulation of sales reports. By using the waterfall method which consist of planning, analysis, design, implementation, and maintenance.